Treatment Response Prediction and Individualized Identification of Short-Term Abstinence Methamphetamine Dependence Using Brain Graph Metrics - Yan, Cui; Yang, Xuefei; Yang, Ru; Yang, Wenhan; Luo, Jing; Tang, Fei; Huang, Sihong; Liu, Jun (Frontiers in Psychiatry, 2021)
Background: Worldwide, the abuse of methamphetamine (MA) has gained international attention as the most rapidly growing illicit drug problem. The classification and treatment response prediction of MA addicts are therefore paramount, in order for effective treatments to be more targeted to individuals. However, there has been limited progress. Methods: In the present study, 43 MA-dependent participants and 38 age- and gender-matched healthy controls were enrolled. The present study used a machine learning method, a support vector machine (SVM), to construct classifiers for discriminating and predicting the treatment response for MA-dependent participants based on the features extracted from the functional graph metrics. Results: A classifier was able to differentiate MA-dependent subjects from normal controls, with a cross-validated prediction accuracy, sensitivity and specificity of 73.2%(95%CI: 71.23%-74.17%), 66.05%(95%CI: 63.06%-69.04%) and 80.35%(95%CI: 77.77%-82.93%), respectively, at an individual level. The most accurate combination of classifier features include the nodal efficiency in the right middle temporal gyrus, and the community index in the left precentral_gyrus and cuneus. Between these, the community index in the left precentral_gyrus had the highest importance. In addition, the classification performance of the other classifier used to predict the treatment response of MA-dependent subjects had an accuracy, sensitivity and specificity of 71.2% (95%CI: 69.28%-73.12%), 86.75% (95%CI: 84.48%-88.92%) and 55.65% (95%CI: 52.61%-58.79%), respectively, at an individual level. Furthermore, the most accurate combination of classifier features include the nodal clustering coefficient in the right orbital part of the superior frontal gyrus, the nodal local efficiency in the right orbital part of the superior frontal gyrus, and the right triangular part of the inferior frontal gyrus and right temporal pole of middle temporal gyrus. Among these, the nodal local efficiency in the right temporal pole of the middle temporal gyrus had the highest feature importance. Conclusion: The present study identified the best combinations of features to differentiate and predict the treatment response for MA-dependent patients based on SVMs and features extracted from the graph metrics. The brain regions involved in the best combinations should be given close attention during the treatment of MA.